[PP.13.03] ANTIANGIOGENETICS AND HYPERTENSION: MANAGEMENT AND PROGNOSTIC IMPLICATIONS. (September 2016) - Destro, M.; Dognini, G.P.; Cagnoni, F.; Borgonovo, K.F.; Maccagni, G.; Barni, S.
Abstract : Objective: Antiangiogenetics (AAG) are a class of compounds used for cancer treatment that inhibit angiogenesis and induce cancer cells death. A class effect common to all AAG is hypertension (AAG-HTN). Aim of this study was to evaluate cancer patients (pts) receiving an AAG in terms of AAG-HTN features and management. Design and method: Between March 2012 and January 2016, all cancer patients pts receiving an AAG at Treviglio-Caravaggio Hospital (Italy) were evaluated by a multidisciplinary team. Pts evaluation comprised office, home (HBPM) and ambulatory BP measurement. HTN was defined according to the ESH/ESC and NIH/CTCAE criteria and treated according to the ESH/ESC guidelines and to cancer site and renal/liver function, whereas lifestyle modifications were generally not applied because of pts' performance status. Results: Overall 55 consecutive AAG treated pts were evaluated (M/F = 38/17, median age:61, range:48–84yrs). Cancer sites were: colorectal(N = 21), kidney(N = 15), hepatocellular(N = 10), other(N = 9). The employed AAG were: bevacizumab(N = 24), sunitinib(N = 14), sorafenib(N = 13), pazopanib(N = 2), aflibercept(N = 2), regorafenib(N = 2), axitinib(N = 3). Among them, 5 pts received 2 consecutive different AAG and, considering both first and second lines (N = 60), AAG-HTN was observed in 53%(32/60). AAG-HTN control was obtained in 22 (69%) pts, by employing ARB, diuretics, CCB, BB, ACEI, and other drugs (in 16, 16, 15, 7, 5, 3 pts respectively). In 13 pts (59%) AAG-HTN was controlled with 2 to 3 antihypertensives, whereas 6 pts (27%) received 4 or more drugs, and only 3 (14%) received 1 drug. In 9 pts (=27%) a great BP variability was observed according to the timing of AAG administration (alternating HTN to symptomatic hypotension) and AAG-HTN was controlled through strict Home BP monitoring and continuous antihypertensives adjustment. Conclusions: AAG-HTN displays peculiar features compared to general population (i.e. BP variability according to AAG timing), and generally requires a higher number of antihypertensives to obtain BP control (4 or more drugs in 27% pts compared to < 5% in general population). Treatment choice must take in account pts' Performance Status, liver and renal function, and concomitant chemotherapy. BP measurement is crucial, particularly Home BP, and allows to tailor antihypertensive therapy, mainly in pts with high BP variability.